The psychological and symbolic factor of Great Britain’s geostrategy in the Cyprus-Suez issue. - Ioannis Mazis (Regional Science Inquiry, 2014)
In the present paper I argue that, since Cyprus came under the British rule and for at least seven decades, Britain did not consider Cyprus a “territory of major strategic importance for the Crown”. I also argue that the policy makers of colonial Britain probably considered this island one of the “poor colonies”, since it did not have raw material deposits or any kind of industrial infrastructure. Thus, I suggest that Greek researchers should examine how Great Britain was perceiving the strategic importance of Cyprus until the end of World War II and, therefore, should not insist on blaming the Greek side that, supposedly, did not take into account Britain’s sensitivity and “unwisely sought the Union (Enosis) of Cyprus with Greece, which annoyed Britain and led to the well-known traumatic events”.